2021
DOI: 10.3389/fonc.2021.686369
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomal miRNAs in Glioma: Biological Function and Clinical Application

Abstract: Gliomas are complex and heterogeneous central nervous system tumors with poor prognosis. Despite the increasing development of aggressive combination therapies, the prognosis of glioma is generally unsatisfactory. Exosomal microRNA (miRNA) has been successfully used in other diseases as a reliable biomarker and even therapeutic target. Recent studies show that exosomal miRNA plays an important role in glioma occurrence, development, invasion, metastasis, and treatment resistance. However, the association of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 111 publications
0
18
0
Order By: Relevance
“…In addition, it was found that B- and T-lymphocyte attenuator (BTLA) was positively correlated with the expression of macrophages. Blocking BTLA can significantly block the inhibition of T cell proliferation by macrophages [ 48 ]. In addition, blocking PD-L1 can significantly block the inhibition of T cell proliferation by mononuclear phagocytes.…”
Section: Tams and Tumor Microenvironmentmentioning
confidence: 99%
“…In addition, it was found that B- and T-lymphocyte attenuator (BTLA) was positively correlated with the expression of macrophages. Blocking BTLA can significantly block the inhibition of T cell proliferation by macrophages [ 48 ]. In addition, blocking PD-L1 can significantly block the inhibition of T cell proliferation by mononuclear phagocytes.…”
Section: Tams and Tumor Microenvironmentmentioning
confidence: 99%
“…Studies have demonstrated that exosomes have the ability to regulate a variety of complex signaling pathways by mediating small molecules such as miRNAs, which provides a powerful tool for GBM [ 112 , 113 ]. The biological functions of exosomal microRNAs -gene regulatory factors -are different in glioma.…”
Section: Role Of Exosome In Delivery Of Effective Therapeutics For Gb...mentioning
confidence: 99%
“…Exosomal microRNAs have been used successfully as biomarkers and therapeutic targets in other diseases. In recent studies, exosomal miRNA plays an important role in glioma occurrence, invasion, development, metastasis, and treatment resistance [ 112 ]. For precise glioma treatment, the use of exosomal miRNAs in combination with exosomes and transcriptomics is expected to be a new approach [ 112 , 115 ].…”
Section: Role Of Exosome In Delivery Of Effective Therapeutics For Gb...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that plasmin found in the CNS can induce apoptosis of tumor cells; however, breast and lung cancer cell lines highly express neuroserpin, a neuronal inhibitor of plasminogen activator, thereby evading the pro-apoptotic effect of plasmin ( 127 ). This finding may be based on the fact that high levels of chloride in the interstitial fluid have a damaging effect on non-neuronal cells; coupled with the abundant neurotrophic factors, glutamate, and other substances in the CNS, this may induce certain neuronal properties in tumor cells to make them more suitable for survival in the CNS microenvironment ( 128 ).…”
Section: Biological Characteristics Of Tumor Cells In the Brain Metas...mentioning
confidence: 99%